Fertilization Technology of Virginia Tobacco Farmers in Bojonegoro and Lamongan Districts and approach to IoT - Supriyadi, Supriyadi; Fatah, Gatot Suharto Abdul; Putri, Rumanintya Lisaria; Yogi, Yoga Angangga (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The districts of Jember, Bojonegoro, and Lamongan are home to Virginia tobacco shops. In Bojonegoro Regency, there are 11,522 ha and 11,517 ha of tobacco land, while there are 6697 ha and 6683 ha in Lamongan Regency. The quality of tobacco is lowered by excessive fertilization, the use of impure varieties, interplanting with chilies, and the neglectful pruning of shoots (Tirtosastro S and Taufik I, 2022). Inorganic fertilizers used in excess will deteriorate unhealthful soil (Arifin Z and Lolita ES, 2020). The issue of excessive chlorine fertilizer use results in a decrease in tobacco quality (low burning power, dull color). The Bojonegoro and Lamongan regions have lost many tobacco product industries as a result of excessive chlorine fertilizer restrictions on tobacco plants. Based on the aforementioned issues, a survey study on fertilization methods for Virginia farmers in the Bojonegoro and Lamongan Regencies is required. The goal of this study was to ascertain how fertilizers were applied by farmers and to measure the soil's and tobacco leaves' chlorine contents. The fertilization process is carried out with an approach to the Internet of Things which is necessary for fertilization automation and more optimal results.